Risk Factor Identification of Multi-Drug Resistant Tuberculosis - Kurnia Fajar Chasanah; Ika Trisnawati; Wahyudi Istiono (Faculty of Medicine, Public Health, and Nursing, 2022)
Background: Multi-drug resistant tuberculosis (MDR-TB) is a serious health problem with high morbidity and mortality. The identification of risk factors is needed to prevent the incidence TB-MDR. Objective: To identify the risk factors of TB-MDR in the Special Region of Yogyakarta.Method: This study used a case control design to assess the risk factors for the incidence of MDR-TB. Patients diagnosed with MDR-TB compared to non-MDR TB patients were then compared to exposure to the risk factors studied. The results of the study were analyzed by calculating the mean and proportion. Next, Chi-square tests and analysis of odds ratio (OR) with 95% confidence interval (CI) were conducted using a 2x2 dummy table as an aid with multivariate logistic regression analysis.Result: There were 53 patients with MDR-TB as the case group and 106 non-MDR TB patients as controls. There were no significant differences between the two groups regarding the characteristics of age, sex, place of residence, and type of work (p>0.05). The multivariate analysis found the risk factors associated with an increased incidence of MDR-TB were a history of previous TB treatment (p<0.001; OR 31.82; 95%CI: 9.40-107.77) and surrounding TB (p<0.01; OR 4.45; 95%CI: 1.45-13.70), while other factors that were not significantly related to the incidence of MDR-TB included body mass index, distance of home to health facilities where taking medicine, smoking, drinking alcohol, history of BCG vaccination, education, income, medication adherence, and comorbidities (p> 0.05).Conclusion: The risk factors found to be associated with an increased incidence of MDR-TB in this study were the presence of surrounding TB patients and a history of previous TB treatment.